Il ritmo dialitico bisettimanale può essere utilizzato in pazienti selezionati all'avvio del trattamento emodialitico cronico. Issue 2 (June 2018) - Cornacchiari, Marina; Cosa, Francesco; Martina, Valentina; Di Toma, Luca; Gidaro, Barbara; Visciano, Bianca; Stasi, Antonella; Meneghini, Maria; Neri, Annalisa; Guastoni, Carlo
Twice-weekly emodialysis can be scheduled for patients selected at the start of the dialysis treatment. In recent years, several studies have evaluated the differences in survival and residual renal function between patients who underwent two times weekly haemodialysis (HDB) and three times weekly haemodialysis (HDT). In most cases, these studies have taken into account only the patient survival but not the time into treatment or "technique survival". In our centre we have retrospectively evaluated the incident patients that were treated with HDB for at least three months between 01 January 2013 and 01 November 2015, focusing on the HDB technique survival. During the follow-up, 35 patients started treatment with HDB, while 13 with HDT. On average, patients treated with HDT were younger than HDB patients (60.9±15.9 years vs. 77.8±9.6 years, p=0.01), and body weight was higher in HDT patients (71±8 kg vs. 63±13 kg, p=0.01). HDT patients were more frequently affected by two or more comorbidities (diabetes, peripheral vasculopathy, cardiac disease, chronic obstructive lung disease) than patients treated by HDB. The creatinine clearance (CrCl) evaluated at the beginning of treatment was similar in the two groups (7.48±5 mL/min in HDB vs 5.4±5 mL/min in HDT, p=NS). Urine output at the beginning of the study was higher in the HDB than the HDT group (1, 785±480 mL/24 h vs. 530±500 mL/24 h, p=0.001).Results . The mean survival of the HDB was 14.9±1.5 months (ranging from 12 to 17.9 months, median 14±2.4 months). During the follow-up period, 12 patients switched from HDB to HDT due to the presence of signs of fluid overload in ten of them. In these patients the CrCl and the urine output were significantly reduced by the end of the treatment (CrCl was 3.4±1.9 mL/min vs 6.8±2 mL/min, p=0.01; urine output was 995±567 mL/24h vs 1400±400 mL/24h, p = 0.02). No hospital admissions for uremic symptoms (pericarditis, pulmonary oedema, severe hyperkalaemia) were recorded throughout the follow-up period in HDB patients.Conclusions . Our study shows that HDB can be proposed in selected patients for a considerable period. Decrease of urine output and presence of symptoms related to fluid overload are the two main factors leading to the switch to HDT treatment.